PENERAPAN AKUNTANSI MANAJEMEN LINGKUNGAN TERHADAP KINERJA KEUANGAN: KINERJA LINGKUNGAN SEBAGAI PEMEDIASI - ROFI DINNILAH AFAZIS; SUSI HANDAYANI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2020)
This study aims to examine the mediating effect of environmental performance on the link between environmental management accounting and financial performance. The research sample is 29 companies listed in Indonesia Stock Exchange for the period 2017-2018. The data analysis technique used are path analysis and sobel test with Statistical Package for Social Sciences (SPSS) 22 programs. The result of this research show that the application of environmental management accounting has no effect on environmental performance and environmental performance has no effect on financial performance, so it can be conclude that environmental performance cannot mediate the relationship between environmental management accounting and financial performance.